Assessing the effects of vegetable consumption on the psychological health of healthy adults: a systematic review of prospective research. Issue 1 (1st June 2019) - Tuck, Nicola-Jayne; Farrow, Claire; Thomas, Jason M
ABSTRACT: Background: To alleviate the immense health and economic burden of mental illness, modifiable targets to promote psychological health are required. Emerging evidence suggests that both fruit and vegetable (F&V) consumption may play an important role. However, the precise contribution of vegetable consumption, which may represent a more potent target than the consumption of fruit, has received little attention. Objectives: This review aimed to synthesize and evaluate research investigating the effects of vegetable consumption on mental health and psychological well-being in nonclinical, healthy adult populations. We aimed to provide insight into the causal relation between vegetable consumption and these outcomes. Methods: Only studies with prospective or experimental data were included. The survey of the literature was last implemented on 1 February, 2019. Results: Ten eligible studies were identified, with a total sample size of n  = 33, 645, that measured vegetable intake separately from fruit, or combined this with fruit intake. Where studies explored the independent effects of fruit and vegetable consumption on psychological health ( n  = 3), 2 reported a preferential effect of vegetables (compared with fruit) on psychological well-being, whereas 1 reported a superior effect of fruit intake on odds reduction of symptoms of depression. More broadly, there was evidence that consuming the recommended amount of F&V (and exceeding this) was associated with increased psychological well-being. However, the effects of F&V consumption on mental health symptoms were inconsistent. Conclusions: Increased F&V consumption has a positive effect on psychological well-being and there appears to be a preferential effect of vegetables (compared with fruit) from the limited data examined. The effect of F&V intake on mental health is less clear and, at present, there are no clear data to support a preferential effect of vegetable intake on mental health outcomes. Hence, additional research is warranted to investigate the influence of vegetables, compared with fruit, on psychological health in order to inform nutrition-based interventions. This review was registered at www.crd.york.ac.uk/prospero as CRD42017072880.